KREATIVITAS SRI MUMPUNI DALAM TARI MULIE BEKIPAS DI SANGGAR KUSUMA LALITA METRO LAMPUNG - Fitri Ciptaningsih; Syahrial (Institut Seni Indonesia Surakarta, 2024)
This research aims to describe and show Sri Mumpuni's creativity in the Mulie Bekipas Dance at Sanggar Kusuma Lalita Metro Lampung. The problems in this research include: (1) what is the form of the Mulie Bekipas Dance at the Kusuma Lailta Studio? and (2) how is Sri Mumpuni's creativity in the Mulie Bekipas Dance at the Kusuma Lalita Studio? Thus, to answer this problem, Y. Sumandiyo Hadi's theory is used to discuss the dance form which contains elements of group choreography and to discuss Sri Mumpuni's creativity in this dance work the author uses Rodhes' theory quoted by Utami Munandar, namely person, process (process), press (pusher) and product (product). This research uses a qualitative research method with a choreographic approach. The research stage carried out was data collection by means of observation, interviews and literature study. Then all the data is collected and finally analyzed. The results of the research show that the Mulie Bekipas Dance form is a group dance, which consists of 11 elements which include dance movements, dance space, dance accompaniment/dance music, dance theme, type/kind/nature of dance, mode or method of presentation, number of dancers/type gender and body posture, make-up, lighting/stage lighting, dance props/other equipment. And this creativity is shown in the choreographer, the factors that influenced it, the creation process up to the formation of the Mulie Bekipas Dance.